Management of variceal hemorrhage: current concepts - COELHO,Fabricio Ferreira (2014)
INTRODUCTION: The treatment of portal hypertension is complex and the the best strategy depends on the underlying disease (cirrhosis vs. schistosomiasis), patient's clinical condition and time on it is performed (during an acute episode of variceal bleeding or electively, as pre-primary, primary or secondary prophylaxis). With the advent of new pharmacological options and technical development of endoscopy and interventional radiology treatment of portal hypertension has changed in recent decades. AIM: To review the strategies employed in elective and emergency treatment of variceal bleeding in cirrhotic and schistosomotic patients. METHODS: Survey of publications in PubMed, Embase, Lilacs, SciELO and Cochrane databases through June 2013, using the headings: portal hypertension, esophageal and gastric varices, variceal bleeding, liver cirrhosis, schistosomiasis mansoni, surgical treatment, pharmacological treatment, secondary prophylaxis, primary prophylaxis, pre-primary prophylaxis. CONCLUSION: Pre-primary prophylaxis doesn't have specific treatment strategies; the best recommendation is treatment of the underlying disease. Primary prophylaxis should be performed in cirrhotic patients with beta-blockers or endoscopic variceal ligation. There is controversy regarding the effectiveness of primary prophylaxis in patients with schistosomiasis; when indicated, it is done with beta-blockers or endoscopic therapy in high-risk varices. Treatment of acute variceal bleeding is systematized in the literature, combination of vasoconstrictor drugs and endoscopic therapy, provided significant decline in mortality over the last decades. TIPS and surgical treatment are options as rescue therapy. Secondary prophylaxis plays a fundamental role in the reduction of recurrent bleeding, the best option in cirrhotic patients is the combination of pharmacological therapy with beta-blockers and endoscopic band ligation. TIPS or surgical treatment, are options for controlling rebleeding on failure of secondary prophylaxis. Despite the increasing evidence of the effectiveness of pharmacological and endoscopic treatment in schistosomotic patients, surgical therapy still plays an important role in secondary prophylaxis.